Innovations in Evaluating Nursing Academic Practice Partnerships. (June 2021) - Polancich, Shea; Miltner, Rebecca; Poe, Terri; Harper, Doreen; Moneyham, Linda; Shirey, Maria
Abstract : Academic-practice partnerships are formalized relationships encouraged by the American Association of Colleges of Nursing to meet healthcare and societal needs. While Academic-practice partnerships have existed for decades, the process for evaluating their outcomes often lacks a robust, standardized structure. The purpose of this article is to describe one organization's process for developing and implementing an evaluation blueprint for appraising an Academic-practice partnership. Abstract : Supplemental digital content is available in the text.